ANALISIS KOMPARATIF NILAI PENDIDIKAN MULTIKULTURAL DALAM BUKU PAKET PAI-BP KELAS VI SD/MI ANTARA TERBITAN KEMENDIKBUD DAN KEMENAG - Bey Arifin Sidon; Ahmad Aziz Fanani (MUMTAZ : Jurnal Pendidikan Agama Islam, 2022)
This study aims to analyze and compare the contents of the content of multicultural education values in the student package book "Pendidikan Agama Islam dan Budi Pekerti Kelas VI SD/MI" between the publications of the Ministry of Education and Culture as book 1, and those published by the Ministry of Religion as book 2. This research includes comparative research using a qualitative approach and types of library research. Data collection was carried out by reviewing documents in the form of a package book "Islamic Religious Education and Ethics Class VI SD/MI" published by the Ministry of Education and Culture and the Ministry of Religion. Data analysis techniques include content analysis. Checking the validity of the data is carried out by means of the researcher's diligence technique and the technique of discussing with peers. The results showed that the two books contain multicultural educational values which include; tolerance, justice, equality, democracy, and pluralism, and in book 2 there is an additional value of humanism. Based on the results of this study, it shows that the two books present multicultural education-based PAI material which is a representation of the government's efforts through the Ministry of Education and Culture and the Ministry of Religion to realize the stability of social order, especially in the world of education.